The influence of work motivation, work environment, and job satisfaction on employee performance PT. XYZ - Pramitha, Adila; Riadi, Ridho; Aziz Mubarok, Dadan Abdul; Sarah, Siti (Institute of Computer Science (IOCS), 2024)
This study examines the correlation between work motivation, work environment, and job satisfaction with employee performance at PT XYZ. The research employed a quantitative methodology, employing a descriptive and verificative approach. The sample used in this study consists of a comprehensive total of 35 respondents. To tackle the study issue, the SPSS software is utilized. The study’s findings suggest that employee performance, work motivation, work atmosphere, and job satisfaction could be better. Motivation, work environment, and job happiness have a beneficial impact on employee performance to some extent. Concurrently, the motivation to work, the atmosphere in which work takes place, and the level of happiness with one's employment all benefit employees' performance.